2021
DOI: 10.1007/s00264-021-05101-6
|View full text |Cite
|
Sign up to set email alerts
|

Online educational resources for orthopaedic residency—a narrative review

Abstract: Purpose Residency programs in the medical education field are considered the keystone in the development of aptitude and skills required for practice. With the worldwide current scenario of the COVID-19 pandemic, there has been a shift in the paradigm especially in the teaching of the residents from face-to-face classes to more and more online sessions. The purpose of this study is to present a compendium of knowledge-providing sites, smartphone applications (apps), YouTube channels, and podcasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…31 However, there are very few orthopaedic podcasts that are oriented to the education of trainees, with most of them intended instead for patient education. 32 In 2021, Raja et al found that, of 492 identified online websites with only orthopaedic content, only 16 (3.3%) were directed for orthopaedic learning and not patient education. 32 Of 22 orthopaedic podcasts specifically found in their search, only 9 with similar characteristics were used for final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, there are very few orthopaedic podcasts that are oriented to the education of trainees, with most of them intended instead for patient education. 32 In 2021, Raja et al found that, of 492 identified online websites with only orthopaedic content, only 16 (3.3%) were directed for orthopaedic learning and not patient education. 32 Of 22 orthopaedic podcasts specifically found in their search, only 9 with similar characteristics were used for final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue which most of the teachers mentioned in the findings was that they were unable to evaluate students learning and understanding during online classes as they sought help from their parents and elder siblings during the assessment period. Raja, et al, (2021) add that online education has brought forward the issues of cheating during assessments, which becomes uncontrollable at times.…”
Section: Discussionmentioning
confidence: 99%
“…The shifting to online education was a rather problematic task, which failed to allow suitable training for teachers or students to grasp the complications of this new way of education (Raja, et al, 2021). According to him, this quick shift to the new model of education has highlighted the inadequate Approaches Towards Learning (ATL) skills of teachers, because of which students are unable to deal with it.…”
Section: Problems Encountered By Teachers During Online Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article by Raja et al [ 1 ] regarding online education resources for orthopedic residents with keen interest. As students who entered medical school while our country was deep in the COVID-19 pandemic, we have direct experience consulting the internet for our medical questions, advice, and education materials.…”
mentioning
confidence: 99%